Clinical whole-genome sequencing from routine formalin-fixed, paraffin-embedded specimens: pilot study for the 100, 000 Genomes Project. (October 2018) - Robbe, Pauline; Popitsch, Niko; Knight, Samantha; Antoniou, Pavlos; Becq, Jennifer; He, Miao; Kanapin, Alexander; Samsonova, Anastasia; Vavoulis, Dimitrios; Ross, Mark; Kingsbury, Zoya; Cabes, Maite; et al.
Abstract Purpose Fresh-frozen (FF) tissue is the optimal source of DNA for whole-genome sequencing (WGS) of cancer patients. However, it is not always available, limiting the widespread application of WGS in clinical practice. We explored the viability of using formalin-fixed, paraffin-embedded (FFPE) tissues, available routinely for cancer patients, as a source of DNA for clinical WGS. Methods We conducted a prospective study using DNAs from matched FF, FFPE, and peripheral blood germ-line specimens collected from 52 cancer patients (156 samples) following routine diagnostic protocols. We compared somatic variants detected in FFPE and matching FF samples. Results We found the single-nucleotide variant agreement reached 71% across the genome and somatic copy-number alterations (CNAs) detection from FFPE samples was suboptimal (0.44 median correlation with FF) due to nonuniform coverage. CNA detection was improved significantly with lower reverse crosslinking temperature in FFPE DNA extraction (80 °C or 65 °C depending on the methods). Our final data showed somatic variant detection from FFPE for clinical decision making is possible. We detected 98% of clinically actionable variants (including 30/31 CNAs). Conclusion We present the first prospective WGS study of cancer patients using FFPE specimens collected in a routine clinical environment proving WGS can be applied in the clinic.